The effect of students’ online learning experience on their satisfaction during the COVID-19 pandemic: The mediating role of preference - Li, Xinchao; Odhiambo, Flavian Adhiambo; Ocansey, Dickson Kofi Wiredu (Frontiers in Psychology, 2023)
During the peak of the COVID-19 pandemic, nearly all educational institutions globally had to eventually embrace the maneuver of transferring to nearly 100% online learning as a new routine for different curricula. Identifying the elements which influence student satisfaction will allow educational institutions to establish strategies to ensure the quality of the digital transformation. Thus, this study examined the effect of online-learning experiences on satisfaction in the setting of the COVID-19 pandemic in Kenya. The mediating role of students’ preference on the relationship between online-learning experience and satisfaction was also examined. A web-based survey involving 501 respondents was analyzed using IBM® SPSS® and AMOS software platforms. A structural equation model (SEM) was used to analyze the relationships. Results showed that 80% of participants indicated their preference for in-person learning as against 20% for online learning. Students’ satisfaction- SS had a significant positive correlation with online classroom perceived quality- OCPQ (r = 0.267, p = 0.01), acquisition of self-confidence- ASC (r = 0.434, p = 0.01), teaching performance and engagement- TPE (r = 0.407, p = 0.01), and preference for online learning-POL (r = 0.772, p = 0.01) but a negative correlation with internet access and cost -IAC (r = -0.275, p = 0.01). Moreover, while POL positively correlated with OCPQ, ASC, and TPE, it negatively correlated with IAC. Both the structural model for the main effect and the mediation model provided a good fit and confirmed these relationships. Student preference had a significant effect on satisfaction and played a significant mediating role in the relationship between online-learning experience and satisfaction. These findings shed light on the underlying factors that explain students’ online learning satisfaction and provide guidelines for universities and policymakers to make better decisions that enhance students' online-learning experience and satisfaction.